Dissimilar Sequelae Caused by Single Dental Trauma; A Case Report with Long-Term Follow-Up - Alencar, Marisa Nogueira; Carvalho Kowaltschuk , Tatiana; Juglair , Mariana Martins; Kowalczuck , Alexandre Kowalczuck; Carneiro, Everdan; Xavier da Silva Neto, Ulisses; Portela Ditzel Westphalen, Vânia (Iranian Endodontic Journal, 2024)
Immediate care and accurate diagnosis are essential for treating dental trauma. This report presents a 7-year-old boy suffered a bicycle accident with direct trauma to the mouth and extrusive luxation of teeth #11 and #21. The emergency treatment was performed within the first hour. Clinical examinations showed that both teeth exhibited 3 mm extrusion from comparing their incisal edges to their neighboring teeth, had edematous gingiva, showed grade 3 mobility and were painful to percussion. Radiographic exams showed incomplete root formation, widened periodontal spaces along their entire lengths and absence of bone or root fractures. The treatment consisted of immediate repositioning and semi-rigid splinting. After 15 days, tooth #11 exhibited no clinical signor symptom and tooth #21 was diagnosed with pulp necrosis, with an acute dentoalveolar abscess and intraoral edema. Immediate endodontic treatment was initiated (intracanal dressing with calcium hydroxide paste). At 30 days, another pulp sensibility test was performed on tooth #11, which had a negative response. In the same visit, the intracanal dressing of tooth #21 was replaced. The Ca(OH)2 medication was replaced every 6 months until the formation of an apical barrier. The final dressing consisted of gutta-percha and Grossman’s sealer and was placed two and a half years after the first dressing appointment. The extrusive luxation resulted in two different sequelae: complete root obliteration in tooth #11 and anomalous root development after the formation of an apical barrier in tooth #21. The patient received orthodontic treatment after 6 years from the initial treatment with no negative outcome. After 18 years follow-up, both teeth were stabilized with no symptom or sign. It’s important to follow the evolution of every trauma case continuously because the sequelae can be unpredictable.